Our Bodies Are Our Own: Connecting Abortion and Social Policy - Bourgeois, Sonya (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2014)
It has been 25 years since abortion was decriminalized by the Supreme Court of Canada in 1988, as the court struck down Section 251 of the Criminal Code of Canada, and abortion was made available for women to access without the consent of a doctor. This amendment to the Criminal Code of Canada was a significant step for women, who were granted autonomy in reproductive health decisions. While women are able to access abortion in Canada, pro-life advocates continue to attempt to limit reproductive options through anti-abortion legislation and advocacy. Through critical discourse analysis, Canadian pro-life discourse has been examined to understand the strategies used to limit women’s sexual health choices. This study has identified four themes, The Fetus has Rights, Abortion is Traumatic, Women are First and Foremost Mothers, and Women do not Really Need Abortion that are used to present a narrative about femininity, reproductive health choices, and abortion. Through understanding pro-life discourse and bringing abortion access into social policy, we can work to ensure that women continue to have access to abortion in Canada.RésuméIl ya 25 ans que l’avortement etait décriminialisé par le Cour Supreme du Canada et l’article 251 de le Code Criminel du Canada a été invalidé. Depuis lors, les femmes ont eu accès à l’avortement sans le consetement d’un medicin. L’amendement de 1988 marque une étape importante pour les femme qui, á ce period là, ells étaient accordés l’autonomie dans leurs décisions [de] la santé de la réproduction. Bien que les femmes sont libre d’accéder l’avortement au Canada, les avocats pro-vie continuent à limiter les options reproducteurs des femmes à travers de la législation anti-avortement. Le discours pro-vie est examiné critiquement dans cet article afin de comprendre les stratégies utilisé pour limiter les choix de santé sexuelle des femmes. Il identifie quatres thèmes: les droits de fœtus; la avortement c’est traumatisant; les femmes sont d’abord et avant tout des meres; et les femmes n’ont pas besoin de l’avortement; qui sont utilisé pour presenter un récit negative sur la féminité, leurs choix de santé sexuelle, et l’avortement.